Enhanced electrochemical biosensing efficiency of silica particles supported on partially reduced graphene oxide for sensitive detection of cholesterol - Abraham S.; Srivastava S.; Kumar V.; Pandey S.; Rastogi P.K.; Nirala N.R.; Kashyap S.; Srivastava S.K.; Singh V.N.; Ganesan V.; Saxena P.S.; Srivastava A. (My University, 2025)
The present work introduces partially reduced graphene oxide (pRGO)-silica (SiO2) particles hybrid system (pRGOSHs) for sensitive and cost effective free cholesterol detection. Fabricated out of thin layers of pRGOSHs, these proposed ChOx/pRGOSHs/ITO based biosensors have a detection range of 2.6-15.5 mM with an appreciable detection limit of 1.3 mM and sensitivity of 11.1 μA/mM/cm2. Low Michaelis-Menten constant (Km) (4.9 × 10- 4 mM) and high diffusivity constant (D) (3.2 × 10- 10 cm2/s) values clearly indicate enhanced immobilization of enzyme over the substrate. Additionally, electrochemical impedance studies indicate that the synergistic combination of SiO2 and pRGO also results in much lower impedance values (40% and 18% decrease in comparison to SiO2 and pRGO respectively) for an overall enhanced sensing performance. These results are further corroborated by the density functional theory based theoretical simulations indicating enhanced electron density (theoretically) in case of the proposed hybrid system. Finally, the present work also highlights the importance of Si-OH bonds formation in the proposed pRGOSHs composite system for attaining such enhanced biosensing ability. © 2015 Elsevier B.V.